Spatially Resolved Heterogeneous Electrocatalyst Degradation in Polymer Electrolyte Fuel Cells Subjected to Accelerated Aging Conditions. Issue 11 (1st November 2022) - Sharma, Preetam; Bera, Bapi; Aaron, Douglas; Besli, Muenir Mustafa; Kuppan, Saravanan; Cheng, Lei; Braaten, Jonathan; Craig, Nathan; Stewart, Sarah; Metzger, Michael; Johnston, Christina; Mench, Matthew M.
Abstract : This work quantifies in-plane spatial heterogeneity (polymer electrolyte fuel cell cathode inlet vs outlet) in Pt particle size growth and distribution as a function of nitrogen (N2 ) flow rate during a square-wave accelerated stress test (AST). The average Pt particle sizes for membrane electrode assemblies (MEAs) subjected to N2 flow rates ranging from 4–16 sccm cm −2 are in the range 9–10.5 nm at the end-of-life (EOL) with similar electrochemically active surface area (ECSA) loss (∼65%). However, Pt particle size at EOL exhibits spatial heterogeneity: greater Pt particle size growth occurs near the flow field outlet than the inlet. The spatial heterogeneity for a fully-humidified N2 flow is believed to originate from non-uniform humidification (outlet is more humidified than the inlet) across the cell for a co-flow arrangement. A first-order rate model for ECSA loss predicts linear increase of the rate constant with N2 flow rate. The polarization losses of the aged MEAs over a wide range of operating conditions increase with N2 flow rate. From the results of this work, for holistically assessing durability of Pt catalysts in fuel cells at high humidity conditions, it is recommended to include purge gas flow rate as a stressor during an AST.